Analytical Modelling and Verification of Bus-Clamping Modulation Technique for Switched-Capacitor Converter. (8th February 2017) - Yalavarthi, Amarnath; Ahmad, Akbar
Abstract : Space vector modulation techniques have advantages of high output voltages and reduced harmonic content as they utilize the dc bus effectively. Bus-clamped pulse width modulation classified in space vector techniques has the ability to reduce the switching losses of the converter and has reduced harmonic distortion. This paper provides mathematical analysis for 60-degree bus-clamping strategy to obtain the complete closed-form solution for finding the harmonic coefficients using double Fourier integral expression. The effectiveness of the bus-clamped approach on switched capacitor based multilevel inverter has been shown with comparison to Sinusoidal PWM. The DSP controller TMS320F240 has been chosen for the real-time implementation of 60-degree bus-clamping modulation technique. Simulation and experimental results of the prototype are presented for RL load at different modulation indices showing the superiority of the configuration to cascaded multilevel inverter.